2016
DOI: 10.1038/srep21736
|View full text |Cite
|
Sign up to set email alerts
|

Unique antitumor property of the Mg-Ca-Sr alloys with addition of Zn

Abstract: In clinical practice, tumor recurrence and metastasis after orthopedic prosthesis implantation is an intensely troublesome matter. Therefore, to develop implant materials with antitumor property is extremely necessary and meaningful. Magnesium (Mg) alloys possess superb biocompatibility, mechanical property and biodegradability in orthopedic applications. However, whether they possess antitumor property had seldom been reported. In recent years, it showed that zinc (Zn) not only promote the osteogenic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…Similarly, the Mg–0.3Ca–0.3Zn also showed a better age‐hardening response as compared to Mg–0.3Ca . The addition of Zn to Mg–Ca–Sr improved the antitumor property of the Mg–Ca‐based alloys for the biomedical application . Mg–2Ca–0.5Mn–2Zn showed better corrosion resistance as compared to Mg–2Ca and Mg–4Ca in Kokubo solution.…”
Section: Mg and Its Alloysmentioning
confidence: 90%
“…Similarly, the Mg–0.3Ca–0.3Zn also showed a better age‐hardening response as compared to Mg–0.3Ca . The addition of Zn to Mg–Ca–Sr improved the antitumor property of the Mg–Ca‐based alloys for the biomedical application . Mg–2Ca–0.5Mn–2Zn showed better corrosion resistance as compared to Mg–2Ca and Mg–4Ca in Kokubo solution.…”
Section: Mg and Its Alloysmentioning
confidence: 90%
“…Implantation of Mg scaffold is a promising solution for the treatment of OS due to the following reasons: (1) the released Mg 2+ promotes proliferation of osteoblast in vitro and accelerates the repair of premature bone in vivo [11,12]; (2) degradation products of Mg exhibit anti-tumor properties in vitro [13], and these degradation products are welltolerated in vivo; (3) the in vivo degradation cycle of Mg can be tuned from six months to several years, which matches the long-term treatment cycle of OS [14][15][16]. Previous studies demonstrated that the degradation of Mg releases Mg(OH) 2 and elevates the alkalinity of the cell culture medium [17], by which the tumor cells were killed [18,19]. However, it remains unknown if the increased alkalinity can be maintained in vivo, where the pH buffer system in the body may dampen the antitumor effect.…”
Section: Introductionmentioning
confidence: 95%
“…Recent reports suggest that various alloying elements can enhance the cytotoxic properties of magnesium. Wu and coauthors studied the cytotoxic effect of alloy Mg–Ca–Sr–Zn on the osteogenic sarcoma cell line U2OS. It was shown that Mg–1Ca–0.5Sr– x Zn ( x = 0, 2, 4, 6 mass %) alloys inhibit the proliferation, viability, cell cycle, migration, and invasion of U2OS cells.…”
Section: Introductionmentioning
confidence: 99%